The The Influence of Store Atmosphere and Service Quality on Repurchase Decisions at Fore Coffee in Surabaya - Elma Dina Asofa; Hery Pudjoprastyono; Nurkholish Majid (Universitas KH. Abdul Chalim Mojokerto, 2025)
The coffee industry in Surabaya is facing fierce competition as people's enthusiasm for the habit of enjoying coffee increases. This study aims to investigate the influence of Store Atmosphere and Service Quality on consumer choices to make repeat purchases at Fore Coffee located in Surabaya. The independent variables consist of Store Atmosphere (X1) and Service Quality (X2), while the dependent variable is the repurchase decision (Y). This study used a quantitative approach, collecting data through questionnaires. Analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). A total of 130 respondents who had purchased Fore Coffee products at least once in Surabaya participated in the study. The study revealed that store atmosphere and service quality had a positive and significant influence on repeat purchase decisions. This finding suggests that improving the store environment and service experience increases the likelihood of repeat purchases.